istribution Patterns of the Morphology, Species, and Sex in the Stingray Species Complex of Himantura uarnak, Himantura undulata, and Himantura leoparda in Indonesia - Arlyza1, Irma Shita; Solihin, Dedy Duryadi; Soedharma, Dedi (UI Scholars Hub, 2013)
The assessment of the morphology and stingray species distribution of the Himantura uarnak species complex covers eight sampling sites in western and eastern Indonesia as many as 113 individuals. The observation of the reticulate pattern was accomplished by directly checking the dorsal side of the stingrays, and growth observations also carried out. The distribution patterns were analyzed using the principal component analysis (PCA), while the growth patterns were evaluated using correlation analyses. The reticulation patterns of the H. uarnak species complex were highly variable, and the distribution patterns based on the morphological parameters, species, and sex produced four groups. The distribution of the length frequency of H. undulata and H. uarnak showed a range of different sizes. The body length of the female in the western region is relatively longer than the male, while in the eastern region the female revealed a range in relative size showing that the male was longer than the female. The length-weight relationships of the stingrays were negative allometric, indicating a b-value of less than 3. The b-values of both the male and female H. undulata were 1.5860 and 0.4380, respectively; while the male and female H. uarnak were 0.2956 and 0.4376, respectively.